(3GdCUhd GdYdejI aj EOGQI GdeHjYGJ (B/s - (3eYdG, fGLjs ((3YeGf(B: s [(3Ohf fGTQ(B], s, 2007)
(3ebOeI Gdi EOGQI GdeHjYGJ, JfXje GdfTGW GdHjYj, JNWjW GdfTGW GdHjYj, JbOjQ GdeHjYGJ hWQb GdJfHD HgG, Jbjje GdCOGA GdHjYj hGdQbGHI Ydjg, JNWjW Gdbhi GdHjYjI, GNJjGQ hJYjjf efOhHj GdHjY, JOQjH efOhHj GdHjY hGdJfejI egGQGJge, JYhjV hecGaCI efOhHj GdHjY, JMajR efOhHj GdHjY, GdETQGa Ydi efOhHj GdHjYs
(3HHdjhZQGajG(B: (3U(B.297s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs